2022
DOI: 10.14704/nq.2022.20.5.nq22152
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Correlations between Emotional Intelligence Subscales and Adherence to Health Protocols during the COVID-19 Pandemic

Abstract: Introduction: To mitigate the spread of COVID-19 infection, health protocols have been recommended but some people ignore them. Emotional intelligence is a set of skills that help people to cope with the demands of the environment. The Purpose of this study was to examine the relationship between emotional intelligence subscales and adhere to health protocols during Covid-19 pandemic. Method: This cross-sectional study was advertised on social media. 341 participants completed the self-reported questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Their study results imply that people with a high level of emotional intelligence should be less likely to engage in risky behaviors that expose them to a greater risk of catching COVID. More direct evidence on this is provided by a study which found that people with higher emotional intelligence are more likely http://www.open-jim.org http://creativecommons.org/licenses/by/3.0 II to adhere to COVID-19 health protocols (Aliyari, Bakhtiari, & Kianimoghadam, 2022). Scholars have argued that there is a "behavioral immune system" that can help people be resistant to catching COVID-19, and a large-scale empirical study has found that the behavioral immune system is related to following COVID-19 health and safety measures, such as social distancing, avoiding touching one's face, wearing a facemask, and cleaning and disinfecting (Shook et al, 2020).…”
Section: Emotional Intelligence and Coronavirus Infection Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Their study results imply that people with a high level of emotional intelligence should be less likely to engage in risky behaviors that expose them to a greater risk of catching COVID. More direct evidence on this is provided by a study which found that people with higher emotional intelligence are more likely http://www.open-jim.org http://creativecommons.org/licenses/by/3.0 II to adhere to COVID-19 health protocols (Aliyari, Bakhtiari, & Kianimoghadam, 2022). Scholars have argued that there is a "behavioral immune system" that can help people be resistant to catching COVID-19, and a large-scale empirical study has found that the behavioral immune system is related to following COVID-19 health and safety measures, such as social distancing, avoiding touching one's face, wearing a facemask, and cleaning and disinfecting (Shook et al, 2020).…”
Section: Emotional Intelligence and Coronavirus Infection Ratementioning
confidence: 99%
“…Consequently, it is likely that emotionally intelligent consumers will respond to COVID-19 by remaining calm and shopping in a rational manner, thus using social distancing, avoiding crowded places when possible, and using masks and sanitizers even when they are optional, all of which may decrease their probability of catching coronavirus. As the recent study demonstrated (Aliyari et al, 2022), emotionally intelligent people are more likely to follow COVID-19 health protocols and thus to have higher behavioral immunity to COVID-19.…”
Section: Emotional Intelligence and Coronavirus Infection Ratementioning
confidence: 99%
“…Therefore, it is crucial to follow the health protocol correctly. (Farokhah, Ubaidillah and Yulianti, 2021).Emphasize the possible importance of emotional intelligence subscales on adherence to health protocols (Aliyari et al, 2022).…”
Section: Introductionmentioning
confidence: 99%